Transient Leukopenia After Radioactive Iodine Treatment in Patients With Graves’ Disease: A Retrospective Cohort Study - Yamashita, Kaoru (J Endocr Soc, 2021)
CONTEXT: Radioactive (131)I (RAI) for the treatment of differentiated thyroid cancer is known to induce bone marrow suppression, which occurs approximately 1 month after treatment. However, it is unknown whether RAI therapy for Graves’ disease causes bone marrow suppression. OBJECTIVE: This study aimed to evaluate the short- and long-term effects of RAI therapy on bone marrow function in patients with Graves’ disease. METHODS: In this retrospective cohort study, we included patients with Graves’ disease who received RAI therapy only once between 2003 and 2019 at Tokyo Women’s Medical University. Blood cell counts at baseline were compared with counts at 1, 2, 4, 12, 24, 48, 144, and 240 weeks after RAI therapy. Moreover, changes in white blood cell (WBC) count and leukopenia at 1 week after RAI treatment were compared by baseline patient characteristics. RESULTS: We enrolled 48 patients. Leukopenia was observed in 6 patients at 1 week after RAI treatment, and the overall WBC count significantly decreased (P < 0.001) 1 week after the therapy; however, the values were not significantly lower after 2 weeks. Neither red blood cell nor platelet count were significantly altered. Moreover, independent of other factors, the neutrophil count at the baseline was significantly negatively associated with changes in WBC count or the occurrence of leukopenia 1 week after the RAI treatment. CONCLUSION: These data showed that RAI treatment induced transient reduction in the WBC count 1 week after treatment, although WBC levels were subsequently restored.